Method for diagnosing lung cancer - WASSERSTROM, ADAM; FRUMKIN DANNY (2024)
The present invention relates to a method for diagnosing lung cancer. In particular, the present invention relates to a method for identifying lung cancer in a subject by analyzing a biological sample derived from said subject. More specifically, the invention relates to the identification of lung cancer by analyzing DNA from a plasma sample. The method is based on the difference in DNA methylation between normal and lung cancer DNA. Methods and kits for identifying lung cancer in a subject based on alterations in DNA methylation at selected genomic loci are provided. 本发明涉及用于诊断肺癌的方法。具体地，本发明涉及用于通过分析源自受试者的生物样品鉴定所述受试者的肺癌的方法。更具体地，本发明涉及通过分析来自血浆样品的DNA鉴定肺癌。该方法是基于正常和肺癌DNA之间DNA甲基化的差异。提供了用于基于在选择的基因组基因座处DNA甲基化的改变鉴定受试者的肺癌的方法和试剂盒。